The realtionships between, and seasonal variations in physiology, technique, and performance in cross country skiing - Nordby, V. M. Q. (NTNU, 2023)
Aim: The aim of this study was to investigate possible relationships between a) performance, performance-determining factors and, technique and b) seasonal variations in performance and performance-determining factors and, changes in technique.